L’autonymie, en faisant l’école buissonnière - Kleiber, Georges (Neophilologica, 2010)
This volume edited in memory of our beloved friend Stanisław Karolak is an invitation to step into metalinguistic territory of autonymy. Its lofty aim is to illustrate several apparent paradoxes of autonymy (or mention) and find answers for difficulties in linguistic description of this phenomenon.